M34 Cardiovascular safety of nintedanib in subgroups by cardiovascular risk at baseline in the tomorrow and inpulsis trials. (15th November 2017) - Noth, I; Wijsenbeek, M; Kolb, M; Bonella, F; Moros, L; Wachtlin, D; Corte, TJ
Abstract : Introduction and Aim: Nintedanib is a tyrosine kinase inhibitor, a drug class that may be associated with increased risk of arterial thromboembolic events. The efficacy and safety of 52 weeks' treatment with nintedanib versus placebo in patients with IPF were assessed in the TOMORROW and INPULSIS trials. Patients with myocardial infarction in the previous 6 months, unstable angina in the previous month, or stroke in the previous year were excluded. We assessed the effect of CV risk at baseline on the CV safety of nintedanib 150 mg bid. Methods: Incidence rates of major adverse CV events (MACE) in subgroups of patients with a history of atherosclerotic CV disease and/or≥1 CV risk factor at baseline (higher CV risk), and patients with no history of atherosclerotic CV disease and no CV risk factors at baseline (lower CV risk), were analysed using pooled data from the TOMORROW and INPULSIS trials. CV risk factors were defined as hypertension, dyslipidaemia, BMI ≥30 kg/m 2, current/former smoking, and diabetes. MACE were based on fatal adverse events included in the system organ classes "cardiac disorders" and "vascular disorders" in MedDRA; events in the subordinate standardised MedDRA query (SMQ) "myocardial infarction"; stroke based on selected preferred terms from the subordinate SMQs "haemorrhagic cerebrovascular conditions" and "ischaemic cerebrovascular conditions"; and MedDRA preferred terms "sudden death", "cardiac death" and "sudden cardiac death". Results: At baseline, 1107 (89.9%) patients (656 nintedanib, 451 placebo) had higher CV risk and 124 (10.1%) patients (67 nintedanib, 57 placebo) had lower CV risk. In patients with higher CV risk, incidence rates (95% CI) of MACE were 3.88 (2.58, 5.84) and 3.49 (2.10, 5.79) per 100 patient–years in the nintedanib and placebo groups, respectively. In patients with lower CV risk, incidence rates (95% CI) of MACE were 4.78 (1.54, 14.82) and 5.37 (1.73, 16.65) per 100 patient–years in the nintedanib and placebo groups, respectively. Conclusion: In pooled data from the TOMORROW and INPULSIS trials, the incidence of MACE was similar between the nintedanib and placebo groups in patients with higher CV risk at baseline and in patients with lower CV risk at baseline. Please refer to page A262 for declarations of interest in relation to abstract M34.